Antibacterial Activity of Graded Extract of Sikkam Stem Bark (Bischofia javanica Blume) Against Staphylococcus aureus - Shintjia Dewi Agustan; Vera Estefania Kaban; Astriani Natalia Br Ginting; Roy Indrianto Bangar (JURNAL FARMASI DAN MAKANAN, 2026)
Antibiotic resistance in represents a serious global health challenge, driving the search for alternative antibacterial agents from natural sources. The stem bark of the sikkam tree (Bischofia javanica Blume) has bioactive potential, yet systematic evaluation of its antibacterial activity based on solvent polarity remains limited. This study aimed to investigate the antibacterial potential of graded extracts of Sikkam stem bark against Staphylococcus aureus. Extraction was performed by graded maceration and antibacterial activity was assessed using the disc diffusion method, with amoxicillin and dimethyl sulfoxide serving as positive and negative controls, respectively. Phytochemical screening revealed the presence of phenolics, flavonoids, alkaloids, tannins, saponins, steroids/terpenoids, and quinones. Among the tested extracts, the ethyl acetate extract showed the highest yield (44.65%) and exhibited the strongest antibacterial activity, producing an inhibition zone of 13.75 ± 0.09 mm at concentration 500 mg/mL The ethanol extract also demonstrated strong and consistent inhibition zone of 12.90 ± 0.13 mm, while the n-hexane extract showed the lowest activity, with an inhibition zone of 10.86 ± 0.20 mm. This study indicates that ethyl acetate and ethanol extracts of sikkam stem bark have potential as natural antibacterial agents against Staphylococcus aureus.